PHYSICOCHEMICAL AND FATTY ACID PROFILE OF FISH OIL FROM RED SNAPPER HEADS (LUTJANUS MALABARICUS) REFINED FROM VARIOUS NAOH CONCENTRATIONS - Desiana Nuriza Putri; Hanif Alamudin Alamudin Manshur; Teguh Setyawan; Noor Harini (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The red snapper fillet industry only uses 40–50% of its fish meat; the rest becomes waste. Red snapper fillet waste can be used as raw material for fish oil rich in Polyunsaturated Fatty Acid through the extraction process. Extracted fish oil quality can be improved through a neutralization process. This research aims to determine the degree of Baume NaOH that can produce fish oil with the best physicochemical properties. This study used a simple completely randomized design with three replications. The results showed that the difference in the degree of Baume NaOH significantly affected all characteristics of fish oil except yield and density. The neutralization process with the addition of NaOH 16°Be effectively improves the quality of fish oil and can maintain the unsaturated fatty acid content of fish oil. Neutralized fish oil has the characteristics of an acid number of 2.67 mg KOH/g, a peroxide value of 0.79 meq/kg, a p-anisidin number of 1.34 meq/kg, and a total oxidation number of 2.90 meq/kg. Identification of fatty acids and heavy metal contamination in fish oil before and after neutralization showed that the dominant fatty acid in fish oil was in the form of saturated fatty acids (50.58-67.51%) and heavy metal contamination in the form of arsenic 3.61-4.07 ppm.